2018
DOI: 10.15537/smj.2018.2.20974
|View full text |Cite
|
Sign up to set email alerts
|

Asthma prevalence among adults in Saudi Arabia

Abstract: Objectives:To investigate asthma prevalence and to measure asthma symptoms among Saudi adults in Riyadh, Kingdom of Saudi Arabia.Methods:A cross-sectional survey using the European Community Respiratory Health Survey (ECRHS) questionnaire carried out between April and June 2016, among male and female Saudi nationals aged 20-44 years living in Riyadh. Disproportionate cluster sampling method was used. Asthma was defined based on answering “yes” to any of the following: Have you had wheezing when you did not hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 15 publications
(16 reference statements)
6
68
1
Order By: Relevance
“…A national Saudi household survey was conducted in 2013 estimated that the self-reported clinical diagnosis of asthma to be 4.05% [19]. Another survey using the European Community Respiratory Health Survey questionnaire carried out in Riyadh among a total of 2405 Saudi people aged between 20-44 years showed that the prevalence of physician-diagnosed asthma reported was 11.3% [20]. Regarding COPD, the overall prevalence of COPD in Saudi Arabia is 4.2% [21].…”
Section: Resultsmentioning
confidence: 99%
“…A national Saudi household survey was conducted in 2013 estimated that the self-reported clinical diagnosis of asthma to be 4.05% [19]. Another survey using the European Community Respiratory Health Survey questionnaire carried out in Riyadh among a total of 2405 Saudi people aged between 20-44 years showed that the prevalence of physician-diagnosed asthma reported was 11.3% [20]. Regarding COPD, the overall prevalence of COPD in Saudi Arabia is 4.2% [21].…”
Section: Resultsmentioning
confidence: 99%
“…Histamine, prostaglandins, and leukotrienes are released as a result of the degranulation of mast cell bound IgE. IL-5 also acts as a potent regulator for eosinophil proliferation, differentiation, and activation [3,[5][6][7]. Asthma is classi ied in four categories based on the immune cells involved in the mechanism.…”
Section: Asthma Pathogenesismentioning
confidence: 99%
“…It is characterised by a history of respiratory symptoms such as wheezing, dyspnea, chest tightness and cough varying over time and intensity, as well as expiratory air low limitation [1]. Asthma symptoms are either episodic or persistent, affecting up to 18% of the Saudi population and prevalent in both adults and children [2][3][4][5]. Symptom control in the majority of asthma patients is usually achieved with the gold standard regimen, inhaled corticosteroid (ICS), however approximately 20% of patients do not achieve control, increasing mortality, morbidity and overall healthcare cost [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), approximately 235 million individuals worldwide have asthma [2]. Asthma is considered one of the most common chronic diseases in Saudi Arabia, affecting more than 2 million people over the past three decades, possibly as a result of changes in lifestyle, dietary habits, and exposure to environmental factors such as dust, indoor allergens, tobacco, and sandstorms [3].…”
Section: Introductionmentioning
confidence: 99%